Effect of Warm Compress, Ginger Drink and Turmeric Drink on The Decrease in The Degree of Menstrual Pain - Ruri Yuni Astari (JURNAL KEBIDANAN, 2020)
Menstrual pain is a natural condition, but if doesn’t get appropriate treatment, it can be bad for health. Non-pharmacological efforts that can be applied to cope with menstrual pain are warm compress, providing ginger drink and turmeric drink. This study aims to determine the effect of warm compress, ginger drink and turmeric drink on the decrease in the degree of menstrual pain among midwifery students. This was a quasi experimental study with comparative study design. Samples in the study for 3 treatment groups of warm compress, ginger drink and turmeric drink were as many as 27 respondents, respectively. Data analysis used paired t test. The results showed that there was an effect of warm compress ( value=0.001), ginger drink ( value=0.000) and turmeric drink ( value=0.000) on the decrease in the degree of menstrual pain. Of the three treatments, the most effective was warm compress because it provided a decrease in the degree of menstrual pain with a mean value of 2.03, greater than the treatments of ginger drink by 1.4 and turmeric drink by 1.34. Women who experience menstrual pain can apply alternative treatments to relieve pain by using warm compress, ginger drink or turmeric drink.